2022
DOI: 10.1007/s41978-022-00123-9
|View full text |Cite
|
Sign up to set email alerts
|

Retiring from ‘University Life’: Critical Reflections on a Retirement Lifestyle Planning Program

Abstract: While assisting individual workers to prepare or plan for a successful transition to retirement is a key responsibility of human resource (HR) departments, within many large organizations (including universities) preparations related to financial planning are prioritized, with limited evidence of consideration for the lifestyle preparations needed. The purpose of this study was to evaluate a series of leisure education-based webinars focused on supporting university employees to engage in lifestyle planning as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Despite this endorsement of the need for more retirement intervention programs, Leandro-Franca noted that there is a continuing need for a more robust evaluation of them [59]. Relatedly, while there is some evidence of the effectiveness of leisure education interventions to address the needs of people living with ongoing health problems and more generally in preparing for the transition to retirement [64,[68][69][70], there is a need for the continued development and evaluation of innovative individual or group leisure education programs and services that address the complex needs of some individuals facing this transition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this endorsement of the need for more retirement intervention programs, Leandro-Franca noted that there is a continuing need for a more robust evaluation of them [59]. Relatedly, while there is some evidence of the effectiveness of leisure education interventions to address the needs of people living with ongoing health problems and more generally in preparing for the transition to retirement [64,[68][69][70], there is a need for the continued development and evaluation of innovative individual or group leisure education programs and services that address the complex needs of some individuals facing this transition.…”
Section: Discussionmentioning
confidence: 99%
“…Kleiber and Linde reviewed a wide range of retirement and leisure-related evidence to suggest that leisure education address two key goals to support successful adjustment in retirement: (1) consider what is lost in the transition to retirement (e.g., opportunities to express competence) and how leisure can serve as a context for meeting these enduring needs (i.e., to compensate for or replace what is most valued about work); and (2) focus on examining the various ways different forms of leisure can be a 'restorative resource' for health and well-being, including a focus on addressing social needs [63]. To address both goals, Kleiber and Linde suggested that retirement planning programs focus on helping people: (a) deepen self-awareness and clarify values, (b) identify resources or opportunities (e.g., within one's neighborhood or community), (c) have the chance to 'experience' leisure (e.g., leisure sampling), and (d) engage in problem solving that supports making decisions and commitments [64]. The first recommendation is particularly important for people whose attitudes toward time use and leisure may serve as barriers in the transition to retirement and the latter is essential for people experiencing challenges identified earlier.…”
Section: Implications For Public Health Practice: Leisure Educationmentioning
confidence: 99%
See 3 more Smart Citations